Dramatic pain relief and resolution of bone inflammation following pamidronate in 9 pediatric patients with persistent chronic recurrent multifocal osteomyelitis (CRMO) - Reslan Walid; Kaura Deepak; Wei Xingchang; Miettunen Paivi MH; Aguirre Alberto; Kellner James D (BMC, 2009)
Abstract Background Chronic recurrent multifocal osteomyelitis (CRMO) is an inflammatory, non-infectious osteopathy that affects predominantly patients ≤ 18 years of age. There is no uniformly effective treatment. Our objective is to describe clinical, magnetic resonance imaging (MRI), and bone resorption response to intravenous pamidronate in pediatric CRMO. Methods We report our prospectively documented experience with all CRMO patients treated with pamidronate between 2003 and 2008 at a tertiary pediatric centre. Pamidronate was administered as intravenous cycles. The dose of pamidronate varied among subjects but was given as monthly to every 3 monthly cycles depending on the distance the patient lived from the infusion center. Maximum cumulative dose was ≤ 11.5 mg/kg/year. Pamidronate treatment was continued until resolution of MRI documented bone inflammation. Visual analog scale for pain (VAS) and bone resorption marker urine N-telopeptide/urine creatinine (uNTX/uCr) were measured at baseline, preceding each subsequent pamidronate treatment, at final follow-up, and/or at time of MRI confirmed CRMO flare. MRI of the affected site(s) was obtained at baseline, preceding every 2nd treatment, and with suspected CRMO recurrence. Results Nine patients (5 F: 4 M) were treated, with a median (range) age at treatment of 12.9 (4.5-16.3) years, and median (range) duration of symptoms of 18 (6-36) months. VAS decreased from 10/10 to 0-3/10 by the end of first 3-day treatment for all patients. The mean (range) time to complete MRI resolution of bone inflammation was 6.0 (2-12) months. The mean (confidence interval (CI)) baseline uNTX/uCr was 738.83 (CI 464.25, 1013.42)nmol/mmol/creatinine and the mean (CI) decrease from baseline to pamidronate discontinuation was 522.17 (CI 299.77, 744.56)nmol/mmol/creatinine. Median (range) of follow-up was 31.4 (24-54) months. Four patients had MRI confirmed CRMO recurrence, which responded to one pamidronate re-treatment. The mean (range) uNTX/uCr change as a monthly rate from the time of pamidronate discontinuation to flare was 9.41 (1.38-19.85)nmol/mmol/creatinine compared to -29.88 (-96.83-2.01)nmol/mmol/creatinine for patients who did not flare by the time of final follow-up. Conclusion Pamidronate resulted in resolution of pain and MRI documented inflammation in all patients. No patient flared while his/her uNTX/uCr remained suppressed. We propose that pamidronate is an effective second-line therapy in persistent CRMO.